Remarques critiques sur l’historiographie des Choctaw - Benjamin Balloy (Journal de la Société des Américanistes)
Patricia Galloway’s historical work on the Choctaw of the Southeastern United States has mainly focused on their coalescent dynamic as a people. In such ethnogenetic perspective, it is commonly assumed that regional subdivisions of the Choctaw in the 18th century trace back to ancient ethnical boundaries. Furthering the “multiethnic confederacy” hypothesis, Greg O’Brien recently promoted the idea that the conflict of 1748-1750, between a so-called “pro-French” and a so-called “pro-British” faction among the Choctaw, could be analyzed as the persistent effect of such ethnogenesis. This article, through a close examination of early 18th century documentary evidence, questions these lines and calls for a better apreciation of the sociological aspects of such segmentation.